Measuring the Performance of Information Systems In Developing Small Mediums Enterprise Business Function - Hartanto M B; Asmuni I (International Conference on Engineering and Technology Development (ICETD), 2017)
Information systems (IS) function gives strength to all individuals or group in an organisation daily responsible for information systems related activities in the organisation. This paper exposes about the development of measuring models the IS function’s performance based on scorecard and DMSM models that uses some criteria inthe areas of IS success. Several criteria developed based on the frame work of IS function within small and medium enterprises with limitations. This study highlights the importance of IT/IS-Business partnership to increase the performance of the IS function, especially related to the capability of IS function to perform a good quality planning, effective system adaptation and good operational support.